Analisis Keterkaitan Konsep Geografi pada Muatan IPS di Kelas 5 Sekolah Dasar - Ermayanti, Wita (CV. Supernova Office Stationary and Printing, 2024)
The purpose of writing this article is to determine knowledge of the relationship between geographic concepts and social science content in grade 5 elementary school. Writing was carried out using literature studies based on relevant research results. The results of the discussion describe the concept of geography in relation to social studies learning and how to convey it through interactive media.